Nutritional Composition and Untargeted Metabolomics Reveal the Potential of Tetradesmus obliquus, Chlorella vulgaris and Nannochloropsis oceanica as Valuable Nutrient Sources for Dogs - Ana R. J. Cabrita; Joana Guilherme-Fernandes; Inês M. Valente; Agostinho Almeida; Sofia A. C. Lima; António J. M. Fonseca; Margarida R. G. Maia (Animals, 2022)
The growing pet population is questioning the sustainability of the pet food system. Although microalgae may constitute a more sustainable food resource, the assessment of their potential for canine diets is almost non-existent. The present study aimed to evaluate the potential of three microalgae species (Tetradesmus obliquus, Chlorella vulgaris and Nannochloropsis oceanica) grown locally in industrial photobioreactors as alternative food resources for dogs. A detailed characterization of their nutritional composition and metabolomic profile was carried out and related to the nutritional requirements of dogs. Overall, the essential amino acid content exceeded the amounts required for dogs at all life stages, except methionine and cysteine. The three microalgae were deficient in linoleic acid, N. oceanica presented a linolenic acid content below requirements and T. obliquus and C. vulgaris were deficient in arachidonic and eicosapentaenoic acids. The fiber was mainly composed of insoluble dietary fiber. The mineral profile varied greatly with the microalgae species, demonstrating their different potential for dog feeding. Untargeted metabolomics highlighted glycolipids, glycerolipids and phospholipids as the most discriminating compounds between microalgae species. Overall, the results support the potential of T. obliquus, C. vulgaris and N. oceanica as valuable macro- and micro-nutrients sources for dog feeding.